2‐Mercaptoquinoline Analogues: A Potent Antileishmanial Agent. Issue 6 (9th February 2018) - Koley, Suvajit; Tiwari, Neeraj; Neelabh,; Singh, Rakesh Kumar; Singh, Maya Shankar
Abstract: Leishmaniases are endemic in various countries and parasite is developing resistance against available drugs. Thus, development of new drugs against Leishmania is an open area of investigation for synthetic organic chemist. In order to meet this challenge, a series of 2‐mercaptoquinoline derivatives have been synthesized and docked into the active site of Trypanothione reductase (TryR) enzyme required for redox balance of parasite. These were screened on promastigote and intracellular amastigote stages of L. donovani and found to show high levels of antileishmanial activity together with no cytotoxicity. Some of the synthesized compounds tested here, exhibited very steady and promising leishmanicidal activity against both promastigotes & intracellular amastigotes form, and the observations have been superbly supported by the docking results. Abstract : Variety of 2‐mercaptoquinoline derivatives have been synthesized and docked into the active site of Trypanothione reductase (TryR), enzyme essential for redox balance of parasite. These were tested on promastigote and intracellular amastigote stages of L. donovani and found to show high levels of antileishmanial activity together with no cytotoxicity. Some of the compounds displayed very high and promising leishmanicidal activity against both promastigotes & intracellular amastigotes form. The antileishmanial activity interpretations have been excellently supported by the docking outcomes.